Influence of GB virus C on IFN-γ and IL-2 production and CD38 expression in T lymphocytes from chronically HIV-infected and HIV-HCV-co-infected patients - Baggio-Zappia, Giovana Lotici [UNIFESP] (2015)
This study was designed to assess the effect of GB virus (GBV)-C on the immune response to human immunodeficiency virus (HIV) in chronically HIV-infected and HIV- hepatitis C virus (HCV)-co-infected patients undergoing antiretroviral therapy. A cohort of 159 HIV-seropositive patients, of whom 52 were HCV-co-infected, was included. Epidemiological data were collected and virological and immunological markers, including the production of interferon gamma (IFN-γ) and interleukin (IL)-2 by CD4, CD8 and Tγδ cells and the expression of the activation marker, CD38, were assessed. A total of 65 patients (40.8%) presented markers of GBV-C infection. The presence of GBV-C did not influence HIV and HCV replication or TCD4 and TCD8 cell counts. Immune responses, defined by IFN-γ and IL-2 production and CD38 expression did not differ among the groups. Our results suggest that neither GBV-C viremia nor the presence of E2 antibodies influence HIV and HCV viral replication or CD4 T cell counts in chronically infected patients. Furthermore, GBV-C did not influence cytokine production or CD38-driven immune activation among these patients. Although our results do not exclude a protective effect of GBV-C in early HIV disease, they demonstrate that this effect may not be present in chronically infected patients, who represent the majority of patients in outpatient clinics.